Atmospheric water harvesting using functionalized carbon nanocones - Leivas, Fernanda R.; Barbosa, Marcia C. (Beilstein Journal of Nanotechnology, 2023)
In this work, we propose a method to harvest liquid water from water vapor using carbon nanocones. The condensation occurs due to the presence of hydrophilic sites at the nanocone entrance. The functionalization, together with the high mobility of water inside nanostructures, leads to a fast water flow through the nanostructure. We show using molecular dynamics simulations that this device is able to collect water if the surface functionalization is properly selected.
Keywords: atmospheric water harvesting; hydrophilicity; hydrophobicity; nanocones; nanotechnology